(untitled) (Journal of Hama University, 2019)
The study aim at determining the skills of educational communication that should be available in the content of the teacher guide for the third stage curriculum in the kindergarten stage, and to know the availability of these skills in it. The sample included the teacher guide for the third stage curriculum in the kindergarten stage in the second semester of the academic year 2018-2019 . The study use descriptive analytical method, and the tools of the study consist of: a list of educational communication skills, a content analysis tool, and the veracity and honesty of search tools have been verified. The results show that the skills that enhance mathematical communication are acceptable in the target teacher’s manual. The results of the analysis show that the most frequent communication skills in the two parts of the teacher’s manual are the verbal communication skill. The total frequency in the first part is 675 46.3% 54.1% by 47.33%, followed by the containment skill, with total recurrences in the first part 267 by 18.31%, in the second part 174 by 15.22%, and in third place, the reception skill is repeated in the first part 215 by 14.75% , followed by follow-up skill in the first part by repeating 132 vies followed by the skill of body language in the first part with frequency 125 and 8.57%, the follow-up skill in the second part with frequency 86 and 7.52%, and decrease the skill of voice tone and visual communication in the first part (2.74% and 0.27%). In the second part, the ratio of these skills is 9.36% and 5.51%. In light of the results, the researcher recommend strengthening the teacher’s guide with activities and guidance for the use of visual communication skills and sound tone.